Tissues development in stems of Aristolochia clematitis L. in the point of view of multicellular complexes formation - Zofia Puławska (Acta Societatis Botanicorum Poloniae, 2014)
After cytokinesis the cells do not separate but remain within the wall of the mother cell. After a series of divisions a multicellular complex arises. In the stems of Aristolochia clematitis procambium is closer related to protoxylem than to protophloem, and metaphloem is closer related to metaxylem than to protophloem. Since protophloem has a closer common origin with fibre primordia than with the remaining tissues, it cannot be decided unequivocally what is the origin of the fibres or when procambium differentiates. The common origin of the primary vascular tissues is visible in the pattern of the multicellular complexes, whereas the common origin of the secondary vascular tissue developing in the underground several-year-old parts of the stem can be traced in the arrangement of the single radial tiers. Some characteristics of symplastic growth are discussed.